Avaliação de diferentes técnicas de manejo para o controle de gramíneas invasoras em unidade de conservação de cerrado - Castillioni, Karen Patricia [UNESP] (2015)
Biological invasion is considered a major threat to global biodiversity. Aggravated by human activities, the problem of invasions by African grasses has already reached most part of Cerrado. In order to minimize the damage caused by the invasion, it is essential that management techniques are assessed in invaded ecosystems. In this sense, this study aimed to evaluate the efficiency of different management techniques to the control of Melinis minutiflora and Urochloa decumbens in Cerrado areas under natural regeneration at the Experimental Station of Itirapina-SP (ESI), as well as the response of the native plant community to the treatments. In addition, it was analyzed the benefit/cost ratio of each technique in the study area, i.e., the treatment able to lead to the greatest reduction of the invasive species total biomass by monetary unit. The following treatments were tested: Cut (Ct), Herbicide application (He): glyphosate, combination of Herbicide (glyphosate) followed by Cut (He + Ct) and control (Co) (no intervention). The treatments were applied in 4x4m plots (6 replicates/treatment- total of 24 plots for Melinis minutiflora and 3 replicates/treatment- total of 12 plots for Urochloa decumbens). In each plot, we performed the survey of the vegetation cover (%) in the categories: live invasive grass (Melinis minutiflora and Urochloa decumbens), native graminoids, native forbs, native shrubs (≤ 1.5 m), total dead biomass and bare soil in eight subplots of 1x1m. All aboveground biomass was also collected within each sample unit by using a subplot of 0.5x0.5m. Biomass was separated in the laboratory in the following categories: dead and live invasive grass (Melinis minutiflora and Urochloa decumbens), native graminoids, native forbs, native shrubs and dead biomass, then dried (at 70°C for 3 days) and weighed. The surveys were carried out before treatment application and then every four months (total 12 months). To test the...